Towards more sustainable surimi? PCR-cloning approach for DNA barcoding reveals the use of species of low trophic level and aquaculture in Asian surimi. (March 2016) - Galal-Khallaf, Asmaa; Ardura, Alba; Borrell, Yaisel J.; Garcia-Vazquez, Eva
Abstract: In recent years, authentication of commercialized seafood products has become a market priority. In this study, 29 Asian surimi products produced in China, India and Singapore, and commercialized in two Mediterranean countries (Egypt and Spain), were analyzed in order to authenticate species contained in surimi products. Due to the processing treatments, classical identification methods are not effective. Therefore, we conducted two molecular tracing methodologies for species identification: direct sequencing of 16S rDNA PCR products, and DNA mini-barcoding-based PCR cloning for Cytochrome oxidase subunit I (COI), with subsequent plasmid sequencing. In total, 10 fish species corresponding to 7 families were found. The Singaporean and Chinese surimi contained principally species of low trophic levels, like fringe scale sardines Sardinella fimbriata, and other, likely farmed, species such as striped catfish Pangasianodon hypophthalmus . The presence of low trophic level and aquaculture species suggests that current trends in surimi production are moving towards sustainability. The exception was a vulnerable shovelnose ray ( Rhinobatos jimbaranensis) found in one product, which encourages further studies to detect the use of endangered species in such morphologically indistinct food items. We suggest PCR-cloning methodology for efficient species authentication in seafood controls, especially for mixed products. Highlights: DNA barcoding and PCR-cloning are reliable tools for mixed food traceability. Asian surimi contained a mixture of aquaculture and fisheries-derived species. A strong and standardized program should be created for protecting biodiversity patterns.